Characterization of enzymatic modified soluble dietary fiber from tomato peels with high release of lycopene. (February 2020) - Gu, Meidong; Fang, Huicheng; Gao, Yuhang; Su, Tan; Niu, Yuge; Yu, Liangli (Lucy)
Abstract: Tomato peels contain a lot of lycopene with low bio-ability due to the large amount of insoluble fiber. Enzymatic modification could enhance the extraction yield of lycopene and soluble dietary fiber (SDF) of tomato peels dramatically. In this study, the peels were modified by 5% (w/v) Viscozyme L solution at pH 6 and 1:10 (w/v) as the solid-to-liquid ratio for 35 min. Compared with the original tomato peels (O-Peels), the extraction yield of SDF of the tomato peels by enzymatic treatment (E-Peels) was increased by 72.3%. As the results of the monosaccharide composition, molecular weight, and zeta potential showed, the SDF treated by enzyme (E-SDF) had a higher galacturonic acid content, a smaller molecular weight of 7.09 × 10 4 Da, and a lower zeta potential of −37.6 mV than the original SDF (O-SDF). Morphological characters were measured by scanning electron microscopy (SEM) and atomic force microscopy (AFM), and E-SDF exhibited a looser microstructure than O-SDF. Additionally, E-SDF possessed a stronger gelling ability than O-SDF in the presence of Ca 2+ . E-SDF and O-SDF had similar thermal properties, but E-SDF exhibited excellent hydration properties and glucose absorption capacity. Furthermore, the lycopene content of E-Peels was 170.67 mg per 100 g, which was increased by 23.8% compared to the O-Peels. These results suggest that enzymatic treatment is practical as a potential modification to obtain functional food materials from peel waste during the processing of tomato products. The enzymatic treated peels, as a novel food additive, have the prospect of improving health with high contents of lycopene and dietary fibers. Graphical abstract: Image 1 Highlights: The extraction yield of SDF from tomato peels increased by enzymatic modification. E-SDF had stronger gelling ability than O-SDF in the presence of Ca 2+ . Good hydration properties and glucose-adsorption capacity were observed in E-SDF. E-peels had higher content of lycopene than O-peels.